Is There Any Association Between Regular Physical Activity and Ejaculation Time?. - Yildiz, Yildiray; Kilinc, Muhammet Fatih; Doluoglu, Omer Gokhan (Urology Journal, 2018)
Purpose: Premature ejaculation (PE) is a prevalent disorder in males leading to sequelae such as lack of self-confidence, anxiety, depression and unsatisfactory intercourse for these men and their partners. The aim of this study was to evaluate the relationship between ejaculation and physical activity. Materials and Methods: Group 1 comprised 112 participants who took regular physical activity and Group 2 comprised 126 participants with a sedentary lifestyle. The participants were 18-45 years old, same ethnic origin, insame location and had regular sexual activity for at least 6 months. A comparison was made by metabolic equivalents (MET), premature ejaculation diagnostic tool (PEDT) and intravaginal ejaculatory latency time (IELT). Result: The mean age of Groups 1 and 2 was 25.34 years (range, 18-41 years) and 28.49 years (range, 19-45 years), respectively (P = .21). The mean PEDT score was 6.18 in Group 1, and 10.02 in Group 2. Significant differences were found between Groups 1 and 2 (P = .001). The mean MET score of Group 1 was 3448.23 METmin/week (3012-4496 MET- min/week) while the MET score of Group 2 was 201.87 MET- min/week (66-744 MET- min/week) (P = .001). The mean IELT of Groups 1 and 2 were 316.42 s (120-1530 s) and 189.32 s (20-450 s), respectively. The mean IELT was significantly higher in Group 1 (P = .001). Conclusion: The study results demonstrated that PE was less frequent in men that perform regular physical activity compared to those with a sedentary lifestyle. It can be assumed that regular physical activity may be effectual in gaining a sexual life of higher quality. Prospective studies with longitudinal data are needed to further understand the potential relationship between regular physical activity and premature ejaculation.